Rice Field Blue-green Algae of Bongaigaon District, Assam - Das, A.K.; Sarma, G.C. (Our Nature, 2011)
The present study deals with the blue-green algae (BGA) from the rice fields of Bongaigaon district, Assam. 23 species of blue-green algae belongs to 12 genera has been enumerated. Maximum species were found under the genus Nostoc (4), Anabaena (4), which is followed by Scytonema (3) Aphanocapsa (2), Aphanothece (2) and Phormedium (2). Single species was represented by the genera Microcystis, Chroococcus, Merismopedia, Oscillatoria, Aulosira and Calothrix. DOI: 10.3126/on.v8i1.4344